The Implementation of Learning Models Student Team Achievement Division (STAD) in Improving Results Learning Mathematics Eighth Grade of SMP Negeri 2 Praya - Aini Husnida Wulandari; Lalu Isnaeni Rahman; Sartika Hijriati (Linguistics and ELT Journal, 2022)
This research is a classroom action research conducted in class VIII.1 of SMP Negeri 1 Praya. The purpose of this classroom action research (CAR) is to determine the extent to which students' learning outcomes in mathematics are improved by applying the STAD Type Cooperative Learning Method. In this classroom action research (CAR), it is carried out in 2 cycles, from the results of the actions taken; it is proven to be able to improve student learning outcomes by achieving the classical mastery set that is 85%. Classical completeness 71% obtained in the first cycle, can be increased in the second cycle to 100%. In terms of student activity, there was also an increase, namely in the first cycle, the category of quite active increased to a category. The results of this action research indicate that the application of the STAD Type Cooperative Learning Model can improve student learning outcomes in mathematics with completeness reaching 100%.